Vocational education problems in tourism sphere of Azerbaijan - Aliyeva, I. (Економічний вісник Донбасу, 2017)
It is not hard to perceive the dimensions of the effects on the economy of countries as the tourism sector is a challenging area for 33 different sectors. Tourism is seen as the most important alternative to the industry, and the driving forces of economic development in developing countries. In this sense, in order to get more share from the tourism movements, many countries have started to rapidly increase the number of tourism businesses and their capacities with various incentive measures. Due to the labor-intensive nature of the tourism sector, the importance of trained skilled labor force in the tourism sector arises. Individuals shall be taught practical knowledge and skill in every stage of the tourism education. In order to be able to survive in increasing competition environment qualified workforce is one of the basic steps. And this can only be actualized by efficient and qualified tourism education and employing the vocational school of tourism graduates in the sector. Therefore, the research conducted to emphasis the importance of vocational training for fulfilling the need of qualified personals in tourism. It is not hard to perceive the dimensions of the effects on the economy of countries as the tourism sector is a challenging area for 33 different sectors. Tourism is seen as the most important alternative to the industry, and the driving forces of economic development in developing countries. In this sense, in order to get more share from the tourism movements, many countries have started to rapidly increase the number of tourism businesses and their capacities with various incentive measures. Due to the labor-intensive nature of the tourism sector, the importance of trained skilled labor force in the tourism sector arises. Individuals shall be taught practical knowledge and skill in every stage of the tourism education. In order to be able to survive in increasing competition environment qualified workforce is one of the basic steps. And this can only be actualized by efficient and qualified tourism education and employing the vocational school of tourism graduates in the sector. Therefore, the research conducted to emphasis the importance of vocational training for fulfilling the need of qualified personals in tourism. Учитывая тот факт, что туризм является важным сектором в 33 отраслях, нельзя отрицать его влияния на экономику. Туризм, как самая важная альтернатива, рассматривается как движущая сила в экономическом развитии развивающихся стран. В этой связи многие страны начали увеличивать число туристических предприятий различными инициативами, чтобы получить большую долю доходов в туризме. Специализированные кадровые ресурсы играют ключевую роль в туризме, учитывая тот факт, что туризм является человеческим сектором. Важное значение имеет получение практических знаний на всех этапах туристического образования. Наличие квалифицированного персонала является одним из основных шагов для продолжения растущей конкуренции. Это можно сделать только эффективно и профессионально с помощью образования в сфере туризма и трудоустройства выпускников профессионально-технических училищ в этом секторе. Поэтому в этом исследовании подчеркивается важность профессионального обучения для удовлетворения потребностей квалифицированных кадров в туризме.